2021
DOI: 10.4012/dmj.2020-307
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses of histatin-derived peptides immobilized titanium surface using a tresyl chloride-activated method

Abstract: Effects of histatin-derived peptides immobilization by tresyl chloride-activation technique for MC3T3-E1 cellular responses on titanium (Ti) were evaluated. MC3T3-E1 were cultured on sandblasted and acid-etched Ti disks immobilized with histatin-derived peptides, including histatin-1, JH8194, and mixed histatin-1 with JH8194. Surface topography and cellular morphology were examined using a scanning electron microscope. Elemental composition and conformational peptides on Ti surface were examined using energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Makihira et al tested the performance of Ti implants coated with a histatin-derived peptide on edentulous ridges of dogs; histological analysis and microcomputed tomography showed increased trabecular bone formation around the coated implants versus untreated implants (Makihira et al, 2011). Siwakul et al (Siwakul et al, 2021) evaluated cell adhesion, proliferation, osteogenesis-related genes and alkaline phosphatase activity on histatin-coated Ti surfaces; the results showed that the adhesion of cells to the histatin-coated group achieved cell proliferation significantly histatin achieved significantly higher cell proliferation.…”
Section: Titanium Surface Modificationsmentioning
confidence: 99%
“…Makihira et al tested the performance of Ti implants coated with a histatin-derived peptide on edentulous ridges of dogs; histological analysis and microcomputed tomography showed increased trabecular bone formation around the coated implants versus untreated implants (Makihira et al, 2011). Siwakul et al (Siwakul et al, 2021) evaluated cell adhesion, proliferation, osteogenesis-related genes and alkaline phosphatase activity on histatin-coated Ti surfaces; the results showed that the adhesion of cells to the histatin-coated group achieved cell proliferation significantly histatin achieved significantly higher cell proliferation.…”
Section: Titanium Surface Modificationsmentioning
confidence: 99%
“…AMPs are often conjugated with metal biomaterials, particularly titanium, to impart antibacterial properties to implant surfaces. Functionalization of AMPs on titanium surfaces can be achieved through various methods, such as covalent bonding [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [28] , [28] , [29] , [30] ], or physical adsorption [ [31] , [32] , [33] ]. Once the AMPs are functionalized on the titanium surface, they can provide a potent antimicrobial barrier against bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence in the literature of reviews to evaluate the effects of different implant surface modifications on peri-implant bone formation and osseointegration (Makihira et al, 2011;Andrea et al, 2018b;Moussa and Aparicio, 2020;Siwakul et al, 2021) and the known benefit on osseointegration of the use of bioactive molecules (Junker et al, 2009), we have not found meta-analyses that investigate the results in depth, so the aim of our study was to evaluate the role and efficacy of bioactive surfaces on osseointegration. Our meta-analysis limited the research interest to titanium dental implants coated with biomolecules, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Makihira et al tested in edentulous dog mandibles, the osseointegrative capacity of Ti implants coated with a histatin-derived peptide, demonstrating, by histological and micro-CT analysis, increased trabecular bone formation around the coated implants ( Riool et al, 2017 ). Their observations suggest that antimicrobial peptides on Ti implants would decrease bacterial colonization on the implant surface and facilitate osseointegration ( Silva et al, 2016 ; Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%